2023
DOI: 10.1002/ohn.226
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neck Angles in Endoscopic and Microscopic Otologic Surgeries

Abstract: Objective To quantitatively compare the ergonomic risk of otologic surgeries performed with endoscopes and microscopes. Study Design Observational cross‐sectional study. Setting Operating room of a tertiary academic medical center. Methods Intraoperative neck angles of otolaryngology attendings, fellows, and residents were assessed during 17 otologic surgeries using inertial measurement unit sensors. Sensors were attached midline between the shoulder blades and on the posterior scalp of participants and were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Increasing popularity of endoscopic ear surgery has led some to hypothesize about the potential ergonomic benefits associated with the use of the endoscope. Accumulating data suggest some benefit of a “heads-up” approach, though, like the present study, others suggest that high-risk postures are adopted in both simulated endoscopic and microscopic surgery (28). Although more research in otologic applications is necessary, research in other specialties has not shown a universal benefit of endoscopic surgery over open approaches.…”
Section: Discussionmentioning
confidence: 54%
“…Increasing popularity of endoscopic ear surgery has led some to hypothesize about the potential ergonomic benefits associated with the use of the endoscope. Accumulating data suggest some benefit of a “heads-up” approach, though, like the present study, others suggest that high-risk postures are adopted in both simulated endoscopic and microscopic surgery (28). Although more research in otologic applications is necessary, research in other specialties has not shown a universal benefit of endoscopic surgery over open approaches.…”
Section: Discussionmentioning
confidence: 54%
“…Another study by Joo et al found no significant differences in neck flexion and extension angles or time spent in high‐risk neck positions between endoscopic and microscopic surgery. 16 This study found significant differences in all extremity and trunk angles between microscopic and endoscopic surgery. Specifically, microscopic surgery reported significantly higher angles in all categories compared to endoscopic surgery except for in elbow score.…”
Section: Discussionmentioning
confidence: 57%
“… 18 Whereas previous studies have focused on specific key body angles when assessing musculoskeletal disease risk, doing so without considering a plethora of other factors may paint an incomplete and less nuanced picture of bodily positioning during middle ear surgery. 5 , 16 As such, although endoscopic surgery may result in certain improvements in body angle and positioning relative to microscopic surgery, its ergonomic benefits may be incomprehensive and suggest a continued need for ergonomic innovation within otology. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the assessment of the surgeon's position and musculoskeletal discomfort relied on relatively simple methods. Other methods used in ergonomic studies to measure muscular burden or assess movements, if extended to elds other than ophthalmology, include myotonometer, electromyography, inertial measurement unit sensors, and Rapid Entire Body Assessment 43,[47][48][49][50] . Other tools, such as the NASA Task Load Index and the Borg scale, are also reported for assessing the perceived exertion of surgeons 30,48 .…”
Section: Discussionmentioning
confidence: 99%